Implementing Formative Assessments in Teaching German as a Foreign Language in the Philippines - AGCAOILI, NINA RACHEL V. (Philippine Humanities Review; Vol 20 No 2 (2018), 2021)
This paper is an action research focused on two formative assessment techniques conducted in two beginner German language classes at the University of the Philippines. The action research involved the following steps: (1) implementation of “exit tickets” and “flash feedback” formative assessment techniques, (2) documentation of student behavior through pictures and field notes, and (3) elicitation of student perception of the formative assessment technique through a subsequent questionnaire. Results indicate a generally positive attitude towards the formative assessment techniques applied in class, as the students felt more motivated to learn due to the real-time and informal feedback. This paper offers a simplified template for implementing formative assessments in the foreign language classroom, which may encourage other foreign language teachers and researchers to experiment with formative assessments and other alternative assessment techniques that promote critical thinking and autonomous learning. KEYWORDS : German as a foreign language, formative assessments, student motivation, flash feedback, exit tickets